HLJK-Info. (Leuven : Homo- en Lesbienne Jongeren Koepel, 1990)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Dambruggenstraat 204, 2060 Antwerpen ; vanaf 03(1992) 1 : Lange Leemstraat 337, 2018 Antwerpen
Nederlands
Periodiek